Language Policy and the Issue of Arabic Disappearance in Learning Centers (Arab Countries as a Model) - Olayiwola, Abdul Wahab Monsur; Murtadha, Yusuf (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2026)
The vitality of a language within educational institutions reflects a nation's commitment to cultural identity and knowledge transmission. In many Arab countries, the diminishing use of Arabic in schools and universities highlights critical challenges in language policy and planning. This paper aims to highlight the challenges facing the educational systems in Arab countries with regard to language policy and openness to multilingualism, diglossia and globalization, as a result of the ethnic diversity experienced by these countries. This, in turn, could manifest in identity-based assimilation that works to undermine national identity through a profound process of cultural and social integration, such as what Arab educational institutions have recently been undergoing. Accordingly, this paper adopts a descriptive-analytical approach based on observation and interpretation, to draw the attention of the Arab society to the danger of neglecting Arabic language and the necessity of implementing decisions that could regulate the language of instruction, and foster linguistic awareness in order for Arabic to attain prominent position in reality. Furthermore, it adopts the idea of Arabizing science and training teachers in modern educational method, as well as developing curricula that will restore Arabic’s identity, thereby protecting it from the dependency and stagnation that have afflicted most languages.